Generation of RFIC electrode patterns using electron beam lithography and wet etching characteristic of PZT thin film / Suriati Muhamad - Muhamad, Suriati (2014)
This thesis report on fabrication technique of electride pattern using e-beam lithography and wet etching procss on lead zirconate titanate thin film. The patterns were created using Raith software,